Linico! - Aplicativo mobile de descarte de eletrônico - Britto, Karol Cristina Monteiro (Brasil, 2023)
The disposal of electronic waste is one of the most worryingly growing problems today, affecting all countries in the world. Brazil is among the first in the ranking of electronic waste production, however, the country has registered an increase in the amount of electronic waste collected since the national solid waste policy created in 2010 came into force, causing an increase in specific locations. – known as voluntary delivery points (PEV's) – for carrying out the voluntary delivery of these items by the population. However, the number of voluntary delivery points (PEV's) available for delivery in Manaus/AM is not adequate to meet the demand. In addition, the lack of greater dissemination of these places by public and private agencies means that the population does not have the proper knowledge of how and where to dispose of electronic waste correctly. Therefore, the present work aims to make use of digital design, user experience and user interface for the development of an application to facilitate access to electronics delivery points for disposal, sale or donation and collection of items, in addition to informing the population about the dangers of incorrect disposal and encourage city residents with a benefit program. For the development of the project, the Double Diamond tool of the Design Thinking methodology was used, associated with the analysis of similar, CSD matrix, briefing, requirements and parameters, user flow and sitemap, development of low fidelity wireframes and usability tests. In the end, a high-fidelity prototype was developed for the proposed application, demonstrating the flows of the main functionalities, accompanied by the style guide with the interface design guidelines.